Definition of Intelligence (International Journal of Scientific Research and Management (IJSRM), 2023)
It is often wondered what is the relevance and the exact definition of intelligence. It is the question since there is not much application of artificial intelligence in everyday life. This is a simple observation from daily life. This paper tries to deal with that. It gives a simple definition of intelligence that can be used to demonstrate intelligence in daily life and build simple applications that one can use in everyday life.